Desmoplastic Infantile Ganglioglioma: cytologic findings and differential diagnosis on aspiration material - Fadare, Oluwole (BioMed Central, 2005)
BACKGROUND: Desmoplastic infantile ganglioglioma (DIG) is a rare WHO Grade I tumor of infancy that is characterized by large volume, superficial location, invariable supratentoriality, fronto-parietal lobe predilection and morphologically, by an admixture of astroglial and neuroepithelial elements in a desmoplastic milieu. With over 50 cases described, the histologic and radiographic spectrum of DIG has been well-characterized. The superficial location of DIGs may render them greatly amenable to preoperative assessment utilizing aspiration cytology; however, the cytologic features of this rare tumor have only been reported once previously. CASE PRESENTATION: We present herein cytomorphologic findings from the intraoperative aspiration of a typical case of DIG diagnosed in a 1-year-old male. As evaluated on a single liquid-based preparation, the specimen showed low cellularity and was comprised predominantly of a population of dispersed (occasionally clustered) large neuronal cells with eccentrically located hyperchromatic nuclei (which were occasionally binucleated) and abundant unipolar cytoplasm. Rare smaller astroglial cells were intermixed. Despite the tumor's characteristic desmoplastic histologic appearance, no stromal fragments were identified on the aspiration material. CONCLUSIONS: A differential diagnosis is presented and analyzed in detail and it is concluded that when these large neuronal cells are encountered in an aspirate of a brain mass in a child, a combination of clinical, radiologic and immunohistochemical parameters can eliminate most of the differential possibilities.